PERAN GANDA SUBAK UNTUK PERTANIAN BERKELANJUTAN DI PROVINSI BALI (The Double Roles of Subak For Sustainable Agriculture in Bali Province) - Budiasa, I Wayan (Jurnal AGRISEP, 2010)
Agriculture and subak in Bali are interrelated, indicated by subak’s characteristics, i.e. socio-agriculture, religious, economic, dynamic, and autonomous.  But, any global issues and internal problems can become challenges for subak existence and sustainability of agriculture in Bali. Based on the subak characteristics as well as the Instruction of The President of The Republic of Indonesia Number 3 of 1999 concerning The Policy of Irrigation Management Transfer that in the Law of The Republic of Indonesia Number 7 of 2004 called as Participatory Irrigation Management, the subak is very potential to play the double roles, i.e. to manage an irrigation system and to manage a legal business units in the farm level. To have the roles, the restructuring subak is needed for revitalize legal agribusiness in the subak structure. Capacity buildings at management level through some extensions and trainings are useful for agribusiness development in subak. The successful of the double roles of subak are useful to support the sustainability of agriculture in Bali.